Domestic tourism challenges in Botswana: a stakeholders’ perspective - Morupisi, Phemelo (Cogent social sciences, 2017)
The study aimed at identifying and explaining current challenges faced in the development of domestic tourism in Botswana. A review of recent travel patterns by Batswana shows an increasing outbound movement for leisure purposes. This in itself shows a propensity to travel which is an antecedent to tourism engagement. However, the good outbound leisure travel numbers have not translated to domestic tourism consumption. The research used a focus study approach with purposively selected tourism stakeholders to explore the challenges encountered in the development of domestic tourism. A constant comparative method of data analysis was used to analyse the data collected. The findings indicated that domestic tourism in Botswana is lacking behind because Botswana has a mono product tourism offering which is wildlife based and highly priced leaving Batswana with one option of travel which is outbound. The second finding is that the culture of Batswana generally does not involve travelling for leisure activities because they always have to be in their farms and cattle posts. Thirdly the policy which advocates for a high value-low volume approach has resulted in high prices for tourism services in Botswana especially accommodation. In conclusion the study observes that outbound travel by Batswana is a response to lack of choice locally and recommends diversification to the product offering in Botswana to take advantage of this market. Education, awareness campaigns and concessionary rates for residents during off-season are also recommended to sensitise the residents about product offerings within the country and address the affordability issue.